Synthesis of tryptanthrin and deoxyvasicinone by a regioselective lithiation-intramolecular electrophilic reaction approach - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Arkivoc, 2008)
An efficient synthesis of the 4(3H)-quinazolinone-based alkaloids, tryptanthrin and deoxyvasicinone has been achieved in good overall yields by using the strategy of regioselective lithiation-intramolecular electrophilic reaction as a key-step. Both the molecules have been synthesized in just two-steps from readily available starting materials.
Keywords: 4(3H)-Quinazolinone heterocycles; deoxyvasicinone; lithiation-intramolecular electrophilic reaction; tryptanthrin